2014
DOI: 10.1179/1432891714z.000000000985
|View full text |Cite
|
Sign up to set email alerts
|

The effects of scandium on A356 aluminium alloy in gravity die casting

Abstract: In this project, the addition of scandium into A356 aluminium alloy was studied for its effect on the mechanical properties as well as the changes in microstructure and eutectic morphology after casting process. Scandium addition was administered at the weight percentages of 0·2, 0·4 and 0·6. The results obtained in this work revealed that scandium can significantly enhance the mechanical properties of A356 alloy in terms of hardness and tensile strength. In general, the addition of 0·4 wt-% scandium in A356 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…According to Røyset et al [16], Sc precipitation hardening in non-heat treatable alloys may be more feasible. While some research has demonstrated the benefits of including Sc in 3xxx cast alloys [3,25]. For heat treatable alloys, Sc strengthening will be determined by the combined effect of small particle strengthening from Al3Sc and strengthening from a refined grain/dendritic structure.…”
Section: Xrd and Sem-eds Resultsmentioning
confidence: 99%
“…According to Røyset et al [16], Sc precipitation hardening in non-heat treatable alloys may be more feasible. While some research has demonstrated the benefits of including Sc in 3xxx cast alloys [3,25]. For heat treatable alloys, Sc strengthening will be determined by the combined effect of small particle strengthening from Al3Sc and strengthening from a refined grain/dendritic structure.…”
Section: Xrd and Sem-eds Resultsmentioning
confidence: 99%
“…Some research has demonstrated the benefits of including Sc in 3xxx cast alloys. [ 3,26 ] For heat‐treatable alloys, Sc strengthening will be determined by the combined effect of small particle strengthening from Al 3 Sc and strengthening from a refined grain/dendritic structure.…”
Section: Resultsmentioning
confidence: 99%